ELR(+) chemokine signaling in host defense and disease in a viral model of central nervous system disease - Hosking, Martin P.; Lane, Thomas E. (Frontiers in Cellular Neuroscience, 2014)
Intracranial infection of the neurotropic JHM strain of mouse hepatitis virus (JHMV) into the central nervous system (CNS) of susceptible strains of mice results in an acute encephalomyelitis, accompanied by viral replication in glial cells and robust infiltration of virus-specific T cells that contribute to host defense through cytokine secretion and cytolytic activity. Mice that survive the acute stage of disease develop an immune-mediated demyelinating diseases characterized by viral persistence in white matter tracts and a chronic neuroinflammatory response dominated by T cells and macrophages. Early following JHMV infection, there is a dynamic expression of chemokines and chemokine receptors that contribute to neuroinflammation by regulating innate and adaptive immune responses as well influencing glial biology. In response to JHMV infection, we have shown that signaling through the chemokine receptor CXCR2 contributes to host defense through recruitment of polymorphonuclear cells (PMNs) to the CNS that enhance permeability of the blood-brain-barrier (BBB) and facilitating entry of virus-specific T cells into the parenchyma. Further, CXCR2 promotes the protection of oligodendroglia from cytokine-induced apoptosis and restricts the severity of demyelination. This review covers aspects related to the role of CXCR2 in host defense and disease in response to JHMV infection.